Actual state of knowledge to the point of epidemiology, diagnosis and management with cardiac syndrome X - Banach, Maciej; Okoński, Piotr (Przewodnik Lekarza/Guide for GPs, 2005)
The term cardiac syndrome X used Kemp in 1973 for the first time. In spite of many studies and hypotheses the pathomechanism of syndrome X hasn’t been explained so far. The syndrome is characterized by the presence of chest pain, ischemia of heart in the exercise test and normal view of coronary arteries in coronary angiography. The cardiac syndrome X is usually diagnosed in women at about 50 years of age. The nature of pain during syndrome X is often atypical, they appear not during but after the exercise, often during the rest. The prognosis is good as regards both survival and long-term cardiovascular complications. Lon-term observations confirm the beneficial effect of application of calcium antagonists, beta-blockers, there are suggestions that angiotensin-converting enzyme inhibitors and statins might play the favourable effect in treatment o cardiac syndrome X.